Medicine advertisements: evaluation and implementation of cema-community method - Chairun Wiedyaningsih; Nia Primayani; Warastuti . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Non-prescription medicines are advertised widely to general public. These advertisements attempt to influence consumers’ choices about medicines. Since the advertisements rare to give objective information, therefore it may affect people’s perception and have potential harmful effect for public health. In order to improve the use of medicines by general public, the CEMA-community (Critical Evaluation Medicine Advertisement by the community)) was proven effective empower community in evaluating medicine advertisements. The objectives of the study, therefore, were to investigate medicine advertisements, and improve knowledge and skills of participants in critically evaluating medicine advertisements. Medicine advertisements running within the period of study were evaluated and analyzed according to the Indonesian legal requirements. Community empowerment to improve participants’ knowledge and skills was conducted using CEMA-community method. The method consisted of two activites, the first was a brief lecture and the second was small group discussions in a problem-oriented approach. Data on knowledge was obtained by questionnaire. Data on skills was assessed by the number of inappropriate claims they could identify the advertisements. All data was collected at baseline, immediately, and one month after intervention. Medicine advertisements in television media accounted for 15% off all commercials, with 21.53%; 17.98%; 14.17%; and 10.08% being medicine products for influenza, analgesic/antipyretic, supplement, and cough, respectively. Incomplete and misleading information mostly appeared in the advertisements. Intervention study showed that the average of participants’ knowledge in subtopic of medicine misleading was low and could be increased from 34.2 (pretest) with maximum score 100, to 65.3 (post I) and 58.3 (post II). Participants’ skills also improved immediately after intervention and this was maintained at the one month follow up (score means: 3.33; 26.67; 26.67 of maximum score 100, at pre test, post I, and post II, respectively).Key words: medicine advertisements, community empowerment, CEMA-community method, knowledge; skills